PENGARUH BUDAYA KERJA, LINGKUNGAN KERJA DAN KEPEMIMPINAN TERHADAP MOTIVASI KARYAWAN PT. SINAR NIAGA SEJAHTERA - Agus Riyadi; Onsardi Onsardi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2023)
The research objective was to determine the effect of work culture, work environment and leadership on employee motivation at PT. Sinar Commerce Prosperous. This type of research is quantitative research, data collection methods are carried out by using observation, documentation and questionnaires. The sample in this study were 35 employees at PT. Sinar Commerce Prosperous. The data analysis used is multiple linear regression test, determination test and hypothesis test. The results showed that work culture has a positive effect on employee motivation at PT. Sinar Commerce Prosperous. The work environment has a positive effect on employee motivation at PT. Sinar Commerce Prosperous. Leadership has a positive effect on employee motivation at PT. Sinar Commerce Prosperous. Work culture (X_1), work environment (X2), and leadership (X3) together have a positive effect on employee motivation (Y) at PT. Sinar Commerce Prosperous. Keywords: Work culture, work environment, leadership, motivation